Renewable Energy Integration 2017
DOI: 10.1016/b978-0-12-809592-8.00012-3
|View full text |Cite
|
Sign up to set email alerts
|

Global Power Grids for Harnessing World Renewable Energy

Abstract: The Global Grid advocates the connection of all regional power systems into one electricity transmission system spanning the whole globe. Power systems are currently forming larger and larger interconnections. Environmental awareness and increased electricity consumption leads more investments towards renewable energy sources, abundant in remote locations (off-shore or in deserts). The Global Grid will facilitate the transmission of this "green" electricity to load centers, serving as backbone.This chapter ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The transatlantic link between INL and RWTH was established by a long distance HVCD line with both RWTH and INL laboratory simulating one converter station. The rationale behind this choice is the vision of Global Grid, a globally interconnected power grid based on Ultra HVDC lines connecting continents across the globe [10]. HVDC link allows for interconnection of grids with different system frequencies.…”
Section: Geographically Distributed Real-time Simulationmentioning
confidence: 99%
“…The transatlantic link between INL and RWTH was established by a long distance HVCD line with both RWTH and INL laboratory simulating one converter station. The rationale behind this choice is the vision of Global Grid, a globally interconnected power grid based on Ultra HVDC lines connecting continents across the globe [10]. HVDC link allows for interconnection of grids with different system frequencies.…”
Section: Geographically Distributed Real-time Simulationmentioning
confidence: 99%
“…In order to overcome this problem, a possibility is to employ an additional transformation of coordinates so that the resulting system is characterized by time-invariant steadystates. In order to determine the appropriate transformation to be employed, an analysis of the oscillations of the steady-states arising from (2) has been carried-out in [12]- [14], further validated by extensive simulations. In particular, under the above mentioned requirements, it was shown that the following approximations hold at steady-state conditions:…”
Section: V σmentioning
confidence: 99%
“…One possibility is to conceive new architectures that will take place at the boundary of the existing infrastructure, both at the low-and high-voltage levels. At the high-voltage level, a transmission system spanning the whole planet and connecting most of the large power plants in the world has been proposed, the so-called global grid or supergrid concept [2]. In this scheme it would be possible to integrate remotely located, high potential, aggregated renewable energy resources providing sustainable energy to the main grids by means of multi-terminal high-voltage direct-current (MT-HVDC) transmission systems [3].…”
Section: Introductionmentioning
confidence: 99%
“…The above described advances of a maturing offshore wind energy sector make it now appear realistic that in the near-future offshore wind projects could technically and commercially be viable on the high seas. Such scenario has been theoretically envisaged in the context of their proposed global grid electricity network (Chatzivasileiadis et al, 2014(Chatzivasileiadis et al, , 2013. However, the location of potential high seas offshore wind parks was indicative only and remained on the conceptual level.…”
Section: Introductionmentioning
confidence: 99%